Physical prototypes in cross functional team collaboration: A study of the Model-T2 concept car project - Datta, Sambit; Hanafin, S.; Rolfe, B.; D'Souza, T. (Taylor and Francis, 2011)
Virtual and physical prototypes play a significant role in the design of artifacts. This is particularly true in cross-functional team collaboration, where diverse disciplines come together to contribute to the concept, design and development of an artifact. While the role of prototyping in design and cross-functional collaboration has been widely studied independently, little is known of the role that physical prototypes play during cross-functional team collaboration. This paper reports on a study of virtual and physical prototyping strategies used by a cross-functional team comprising engineers and designers working on a concept car project. The paper provides a background of the collaborative design process and details the role of physical prototyping methods during the design of the concept car.